Gender Roles and Translation in the Book of Proverbs - Bellis, Alice Ogden 1950- (2024)
The editors of Proverbs structured the book to counter traditional negative sentiments about women. Proverbs such as 19.13, “a stupid child is a ruin to a father, and a wife’s quarreling is a continual dripping of rain” (NRSVue), are misogynistic, presenting problems for the contemporary reader and arguably for the ancient editor as well. Their strategy to combat these old sayings included beginning and ending the book with positive feminine figures, Wisdom in the prologue (Prov 1–9) and the Strong Woman in Prov 31.10-31, and using negative masculine stereotypes as a foil for the negative feminine ones. Recent translations that use gender-neutral language mask these tropes about men’s behavior.
Keywords: Gender Roles; Translation; EDITORS; Misogyny; Strong Woman; gender-neutral; proverb; Wisdom; Proverbs